Photocatalytic degradation of oxytetracycline using TiO2 under natural and simulated solar radiation - João H. O. S. Pereira (2011)
The main objective of the present study was to assess the photocatalytic degradation over TiO2 of an aqueous solution containing 20 mg L-1 of the antibiotic Oxytetracycline (OTC) using simulated solar radiation, seconded by a solar radiation experiment carried out in a pilot plant equipped with Compound Parabolic Collectors (CPCs) under the optimal conditions found in preliminary lab-scale experiments. These comprehended a set of 1 L aqueous experiments with TiO2 loads ranging from 0.1 to 0.5 g L-1 starting from different initial pH values. These experiments were carried out in a Solarbox equipped with a 1000 W Xe-OP lamp. OTC degradation was followed by HPLC-DAD, while its mineralization was followed by the removal of Total Organic Carbon. Results suggested that 0.5 g L-1 of TiO2 with no initial pH adjustment (pH similar to 4.4) was the best combination for the removal of both OTC (100% after 40 min of irradiation; 7.5 kJ L-1 of UV dose) and TOC (>90% after 180 min of irradiation; 38.3 kJ L-1 of UV dose). Under these conditions, the BOD5/COD ratio rose from almost 0 to nearly 0.5, showing a remarkable improvement in biodegradability, while inhibition percentage of bioluminescence of Vibrio fischeri after 15 min of exposition measured by Microtox (R) decreased significantly from 35% down to 7%. A scheme of the OTC degradation pathway is proposed, based on the results obtained from this particular experiment. The solar photocatalytic experiment done under the same conditions was carried out in a solar pilot plant equipped with CPCs. OTC and TOC removal was followed as a function of accumulated UV energy entering the reactor. Results showed a 100% OTC and almost 80% TOC removal with 1.8 kJ L-1 and 11.3 kJ L-1 of photo treatment energy, respectively.